Long term forecasts of the supply and demand of anicultural and livestock products in venezuela (Jerusalem : The U.S. Department of agriculture, 1964)
This present study is destined to form part of the long-term evaluation, on a world wide scale, of supply and demand of agricultural and livestock products, undertaken by the department of agriculture of the United States.
ahz 18/03/2019
Loans
Keywords: Economic Development; Venezuela